An Approach To the Fifth Five Year Plan Government of Tripura - Planning Commission (Planning Commission, 1972)
As mentioned earlier, there is a need for popularising raising of cash crop. There is potentiality of bringing much more area under jute and sugarcane cultivation and it is possible to contemplate a considerable development of fruits and nuts on the hills, Before partition, Tripura used to supply a large market in East Bengal with pine-apples, which though small were highly popular for their sweetness.
Government of Tripura Development (Planning and Coordination) Department
Government of Tripura Development (Planning and Coordination) Department